Analisis Proses Belajar Dari Rumah (BDR) Selama Pandemi Covid-19 - Dita Nur Oktaviani; Nur Hudah (Pedir Research Institut, 2021)
Abstract: The conditions of the Covid-19 pandemic have affected almost all aspects of human life. Primary school children's education is one of the sectors that has been badly affected by this pandemic. The learning process during the Covid-19 pandemic is listed in the Circular of the Ministry of Education and Culture Number 4 of 2020 concerning Implementation of Education Policies in an Emergency for the Spread of Corona Virus Disease (Covid-19) regarding Guidelines for Implementing Learning from Home (BDR) during the Covid 19 Emergency Implementation of learning from home (BDR) is learning that is followed by students from home at the hours determined by the Madrasah and at hours outside of that to do assignments. The problems that you want to find answers to through this research are: 1. How was the learning process from home (BDR) during the Covid-19 pandemic at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu? and 2. What were the obstacles in the learning process from home (BDR) during the Covid-19 pandemic at Madrasah Ibtidaiyah Miftahul Ulum Sidowungu? This study uses a qualitative method with a case study approach. Data collection techniques using interview methods, observation, and documentation. The data analysis technique uses the theory in Sugiono's book, testing the validity of the data by triangulation and includes references. The results show that the Learning From Home process during the pandemic runs according to the circular of the Ministry of Education and Culture Number 4 of 2020 and the circular of the Ministry of Religion, Gresik district. While the obstacles faced in the Learning From Home process during the pandemic have solutions to solve them.